THE DECISIONAL ROLES OF KIAI IN DEVELOPING THE ECONOMIC INDEPENDENCE OF PONDOK PESANTREN - Hafidh, Zaini; Kadarsah, Deni; Raspatiningrum, Liris; Nurdin (Jurnal Isema : Islamic Educational Management, 2025)
The development of economic independence for Islamic boarding schools (pondok pesantren) has become an urgent necessity in facing the dynamic challenges of social and economic change. These institutions are required not only to rely on donations but also to develop productive enterprises to ensure the sustainability of the institution and the empowerment of the surrounding community. The purpose of this study is to examine the strategic role of the Kiai in managing the pesantren's resources through various decisional roles, such as entrepreneur, disturbance handler, resource allocator, and negotiator, as well as their effects on the economic development of the pesantren. The method used is a qualitative approach with a case study method. Data were collected through document analysis, observation of pesantren business activities, and interviews with pesantren managers. The study also analyzed data from pesantren businesses, including sectors such as fisheries, agriculture, mining, and waste processing. The results indicate that the effective leadership of the Kiai in executing decisional roles contributes significantly to the development of enterprises and the economic independence of the pesantren. The success of pesantren economic ventures not only increases revenue but also creates employment opportunities and empowers the local community. The synergy between leadership, resource management, and negotiation with various external parties is the key to creating pesantren that are independent, sustainable, and competitive in a modern context.